Family care of people with severe mental disorders: an integrative review - Maria Juan-Porcar; Lledó Guillamón-Gimeno; Azucena Pedraz-Marcos; Ana María Palmar-Santos (Universidade de São Paulo, 2015)
OBJECTIVE: to analyze the scientific literature on home-based family care of people with severe mental illness. METHOD: integrative review of 14 databases (CINALH, Cochrane Plus, Cuidatge, CUIDEN, Eric, IBECS, EMI, ISOC, JBI COnNECT, LILACS, PsycINFO, PubMed, SciELO, and Scopus) searched with the key words "family caregivers", "severe mental illness", and "home" between 2003 and 2013. RESULTS: of 787 articles retrieved, only 85 met the inclusion criteria. The articles appeared in 61 journals from different areas and disciplines, mainly from nursing (36%). The countries producing the most scientific literature on nursing were Brazil, the UK, and the US, and authorship predominantly belonged to university centers. A total of 54.12% of the studies presented quantitative designs, with descriptive ones standing out. Work overload, subjective perspectives, and resources were the main topics of these papers. CONCLUSIONS: the international scientific literature on home-based, informal family care of people with severe mental disorder is limited. Nursing research stands out in this field. The prevalent topics coincide with the evolution of the mental health system. The expansion of the scientific approach to family care is promoted to create evidence-based guidelines for family caregivers and for the clinical practice of professional caregivers.